2016
DOI: 10.5578/mb.27898
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Potentially Pathogenic Free-Living Amoebae and Their In Vivo Pathogenicity in Water Supplies of Turkey

Abstract: Free-living amoebae (FLA) are found widely in soil and water in the nature. Among them in which potentially pathogenic for humans and animals are known as "potential pathogenic free-living amoebae (PPFLA)". PPFLA are characterized as the causes of clinical manifestations leading to death especially in immunosuppressed people. Four genus of PPFLA (Acanthamoeba, Naegleria, Balamuthia and Sappinia) are known to be pathogenic to humans. The aims of this study were to investigate the presence of PPFLA in the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Additionally, one study conducted in Sivas reported the isolation, characterization, and pathogenicity testing of FLA from soil and freshwater samples (Akın 2000). The first report to identify Acanthamoeba in well water sediments was documented in Kayseri (Kuk et al 2013), and another study demonstrated FLA in soil and water samples in Kayseri, Bingöl, Erzurum, Elazıg, Kocaeli, Diyarbakır and I ̇zmir provinces (Yazar et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, one study conducted in Sivas reported the isolation, characterization, and pathogenicity testing of FLA from soil and freshwater samples (Akın 2000). The first report to identify Acanthamoeba in well water sediments was documented in Kayseri (Kuk et al 2013), and another study demonstrated FLA in soil and water samples in Kayseri, Bingöl, Erzurum, Elazıg, Kocaeli, Diyarbakır and I ̇zmir provinces (Yazar et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…have been documented from environmental samples in Ankara (Kilic et al 2004); and amoebae have been found in well water from Kayseri (Kuk et al 2013). Recently, other reports have drawn attention to on potentially pathogenic free-living Amoebae (FLA) isolated from water supplies from different provinces (Kayseri, Bingöl, Erzurum, Elazıg, Kocaeli, Diyarbakır and I ̇zmir) in Turkey (Yazar et al 2016), and Acanthamoeba spp. have been found in river water samples from the Black Sea region provided (Koyun et al 2020).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…Çalışmamızda havuz suyu örneklerinin yedisinde, biyofilm örneklerinin beşinde SYA'ya rastlanmış olması ve bir izolatın potansiyel patojen (termotoleran) 12,24 olarak saptanması bu havuzların sağlık açısından riskli olduğunu akla getirmektedir. Nitekim, son yıllarda yapılan çalışmalarda ülkemizin doğal sularında da patojen SYA'nın varlığı gösterilmiştir 25,26 . Bu tip patojen amipleri içeren doğal suların havuz suyu olarak kullanılma ve amiplerin uygulanan dezenfektan konsantrasyonlarına dirençli olma olasılıkları nedeniyle, havuzları kullanan yüzücülerin sağlığının tehdit altında olduğu düşünülmekte ve yapılacak çalışmaların artırılması gerekmektedir.…”
Section: Discussionunclassified
“…Acanthamoeba spp. were found positive ranging from 4.4% to 50% in various water sources such as tap water, ponds, rivers, streams, and water wells in Turkey [25][26][27][28][29]. Acanthamoeba was detected positively 17.3%, 28.8%, 15.9% and 42.9% in Jamaica, Iran, Thailand, and Uganda in tap water sources, respectively [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%